INFORMASI LABA ALIRAN KAS DAN KOMPONEN ALIRAN KAS TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Muhamad Syafii (Jurnal Keuangan dan Perbankan, 2008)
This study was constitute replicated study from Triyono and Jogiyanto (2000) aboutthe association of information content of total cash flows, components of cash flows, andaccounting income with stock prices or stock returns. This study took samples frommanufacturing firms listed in the Indonesia Stock Exchange (BEI) from 2004-2007 that hadpublished audited financial statement. Stock prices used monthly prices from 2004 to 2007.The statistics method used to test hypotheses was a linier multiple regression. The modelconsidered was levels model. The empirical results using the first levels model about theinfluence information of accounting income and total cash flows with stock prices could beexplained that accounting income gave positive influence and significant with stock priceswhereas total cash flows gave negative influence and significant with stock prices. In thesecond model levels about the influence information of cash flow from operating activities,cash flow from investing activities, and cash flow from financing activities with stock prices, itcould explained that separated total cash flows into components of cash flows gave negativeinfluence and significant with stock prices especially cash flow from operating activities andcash flow from financing activities. In the third model levels about influence information ofaccounting income and components of cash flows with stock prices, it could be explained thataccounting income gave positive influence and significant with stock prices whereas componentsof cash flows gave negative influence and significant with stock prices.